Sistem Pakar Rekomendasi Produk Makeup Berbasis Web dengan Metode Forward Chaining - Nikita Christy; Lily Puspa Dewi; Agustinus Noertjahyana (Jurnal Infra, 2019)
As time goes by, more brands of makeup are popping up. From these brands, there are lots of different types of makeup products which are mostly the same. Because of the many new makeup products, buyers often find it difficult to determine which products are suitable for their skin condition. In assisting in the selection of suitable makeup products, a makeup product recommendation expert system is needed by giving questions that are easily understood by the buyer and the buyer will get recommendations for the appropriate products.Makeup product recommendation expert system uses knowledge rule based that uses an expert as a knowledge base to determine the rule. In processing the information that has been given by the user, the forward chaining method is used by checking the facts that lead to conclusions generated from these facts to test the truth of the hypothesis.The results of the application testing for makeup products show that the application can produce recommended makeup products that are in accordance with the wishes of the user. This decision making process also makes it easy for users because it can be accessed from anywhere and at any time.